CD22 Blockage Restores Age-Related Impairments of Microglia Surveillance Capacity - Aires, Vanessa; Coulon-Bainier, Claire; Pavlovic, Anto; Ebeling, Martin; Schmucki, Roland; Schweitzer, Christophe; Kueng, Erich; Gutbier, Simon; Harde, Eva (Frontiers in Immunology, 2021)
Microglia, the innate immune cells of the brain, are essential for maintaining homeostasis by their ramified, highly motile processes and for orchestrating the immune response to pathological stimuli. They are implicated in several neurodegenerative diseases like Alzheimer’s and Parkinson’s disease. One commonality of these diseases is their strong correlation with aging as the highest risk factor and studying age-related alterations in microglia physiology and associated signaling mechanism is indispensable for a better understanding of age-related pathomechanisms. CD22 has been identified as a modifier of microglia phagocytosis in a recent study, but not much is known about the function of CD22 in microglia. Here we show that CD22 surface levels are upregulated in aged versus adult microglia. Furthermore, in the amyloid mouse model PS2APP, Aβ-containing microglia also exhibit increased CD22 signal. To assess the impact of CD22 blockage on microglia morphology and dynamics, we have established a protocol to image microglia process motility in acutely prepared brain slices from CX3CR1-GFP reporter mice. We observed a significant reduction of microglial ramification and surveillance capacity in brain slices from aged versus adult mice. The age-related decrease in surveillance can be restored by antibody-mediated CD22 blockage in aged mice, whereas surveillance in adult mice is not affected by CD22 inhibition. Moreover to complement the results obtained in mice, we show that human iPSC-derived macrophages exhibit an increased phagocytic capacity upon CD22 blockage. Downstream analysis of antibody-mediated CD22 inhibition revealed an influence on BMP and TGFβ associated gene networks. Our results demonstrate CD22 as a broad age-associated modulator of microglia functionality with potential implications for neurodegenerative disorders.